Novel finite element analysis model for three-roller fillet rolling focusing on its strength of accuracy and practicability - Hyeon Min Lee; Hee Man Kwak; Jeong Muk Choi; Hae Ji Kim; Wan Jin Chung; Man Soo Joun (Journal of Materials Research and Technology)
A novel one-third FE analysis model that enables practical and quantitative analyses of the fillet-rolling process with three rollers is proposed. It solves the fundamental problem of numerical solution that depends on the numerical quality of the contact area between the material and roller during the fillet rolling process by stably imposing the one-third fillet load on the material defined by two symmetry planes forming an internal angle of 120°. The novel FE analysis model, based on an implicit elastoplastic finite element method (FEM), is employed to quantitatively explain the reason for the dramatic effect of the fillet rolling on the fatigue life. With the residual stress information embedded into the critical bolt neck corner (CBNC) during the fillet rolling process, the fatigue test is simulated to reveal the stress cycle at the critical point in the CBNC. The mean and alternating values of the maximum principal stress show the reason for the dramatic increase in the fatigue life of the fillet-rolled titanium alloy bolt.